Pentingnya Memahami Karakteristik Siswa dalam Pembelajaran Bahasa Arab - M. Darkun (Institut Agama Islam Negeri (IAIN) Metro, 2019)
In the learning process a teacher is required to know the characteristics of his students, but sometimes he cannot understand the characteristics of students. Understanding of the subject of learning is what teachers or other education personnel must have, to be made a foothold in developing learning models or methods. The purpose of writing this article is to know the importance of understanding the characteristics of students and achieving the learning objectives that have been determined, and knowing the characteristics of students have an important role in the learning process. This study uses descriptive qualitative research methods. This research includes textual research or text studies and is purely biblical, because the data sources are various references that discuss student characteristics and student learning models, as well as references related to learning Arabic. Because the results of this study are in the form of an explanation of the systematic description of the word as a result of understanding and analysis of the object of research, the study includes descriptive research. The results of this study are the characteristics of students can be collected in two aspects, namely: learning styles. While children's learning styles in general are learning as character building tools and the best intelligence for students, namely: auditory (learning by hearing), visual (learning by seeing), and kinesthetic (learning by doing). And the application in learning Arabic Language writer adjusts to the model / learning style of students.